1974
DOI: 10.1002/pssa.2210250221
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance in diamond implanted at various energies and temperatures

Abstract: Amorphous carbon layer EPR measurements have been fitted to a model which predicts the critical fluences at which the layer forms for any temperature and ion species; it predicts the layer will not form during nitrogen ion implantation in diamond above 1031°K. A new anisotropic EPR spectrum labeled D‐A4 is observed after hot‐implantation (650°C) with nitrogen ions. It is thought to be a spin‐one‐center arising from a small D‐tensor interaction with 〈111〉 symmetry. Hot implantation suppresses the formation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Morhange et alfound similar annealing behaviour as Brosious et al(1974a). Brosious et al(1974b) found that if the nitrogen ions are implanted at high temperatures (2: 600 "C) the spectra appear to be a superposition of two signals. One is the line observed at room-temperature implantation, while the other is due to a centre A4, which they interpreted as being due to a S = 1 state with small D value and (1 11) symmetry.…”
Section: Defects Introduced By Ion Implantation In Diamondmentioning
confidence: 77%
“…Morhange et alfound similar annealing behaviour as Brosious et al(1974a). Brosious et al(1974b) found that if the nitrogen ions are implanted at high temperatures (2: 600 "C) the spectra appear to be a superposition of two signals. One is the line observed at room-temperature implantation, while the other is due to a centre A4, which they interpreted as being due to a S = 1 state with small D value and (1 11) symmetry.…”
Section: Defects Introduced By Ion Implantation In Diamondmentioning
confidence: 77%
“…Therefore, hot iiiiplantation a t an elevated temperature was indicated as an alternative means to reduce the aniorphous carbon in diamond. I n a subsequent study [ 5 ] we carried out implantations into diamond samples a t temperatures ranging from 25 to 650 "C.…”
Section: Introductionmentioning
confidence: 99%